2011
DOI: 10.1002/ar.21422
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stem Cell Niche and Follicular Renewal in Mammals

Abstract: Stem cell niche consists of perivascular compartment, which connects the stem cells to the immune and vascular systems. During embryonic period, extragonadal primordial germ cells colonize coelomic epithelium of developing gonads. Subsequently, ovarian stem cells (OSC) produce secondary germ cells under the influence of OSC niche, including immune system-related cells and hormonal signaling. The OSC in fetal and adult human ovaries serve as a source of germ and granulosa cells. Lack of either granulosa or germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 100 publications
(189 reference statements)
4
59
0
1
Order By: Relevance
“…The OSE cell layer is considered to be "germinal epithelium" and has characteristics of embryonic stem cells. There are still scholars skeptical of the existence of ovarian germline stem cells in mammals [42], but Bukovsky [43] and Tilly [44] assert that this does not take into account samples of ovarian function and different experimental methods. More persuasive is a finding from Wu Ji with OGCs showing that they make infertile mice produce offspring.…”
Section: Ovarian Surface Epithelium Stem Cells and Neo-oogenesismentioning
confidence: 99%
“…The OSE cell layer is considered to be "germinal epithelium" and has characteristics of embryonic stem cells. There are still scholars skeptical of the existence of ovarian germline stem cells in mammals [42], but Bukovsky [43] and Tilly [44] assert that this does not take into account samples of ovarian function and different experimental methods. More persuasive is a finding from Wu Ji with OGCs showing that they make infertile mice produce offspring.…”
Section: Ovarian Surface Epithelium Stem Cells and Neo-oogenesismentioning
confidence: 99%
“…It should be highlighted that they decided not to carry out any purification step based on the presence of FSHR or some other factor, but considered the isolated GCs as a homogeneous cell population in terms of their stemness. This is an interesting approach since all ovarian somatic cells coexist in the common ovarian niche [8], which can play an important role in maintaining of their stemness.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
“…2). Bukovsky [26] observed that the ovarian stem cell nest has been formed in the early embryonic development period and is composed of non-site specific ovarian Monocyte-derived cells (MDCs), T cells and vascular endothelial cells whereas the adult ovarian reproduction stem cell nest is made up of primary MDCs (CD14+ MDC), activated MDCs (HLA-DR+ MDC), T cells, etc.…”
Section: The Composition and The Biological Characteristics Of Ovariamentioning
confidence: 99%